Design Thinking: A New Model for Future University Education - Pahari, Bharat Raj (Journal of the Institute of Engineering, 2023)
Human civilization always opted for the comfort and happiness. There are many literatures supporting this perception. There are the evidences that the learning process started from the time of cognitive revolution, the time mankind started communicating each-other. In the course of time, many inventions happened, and technology emerged as strong tools for the maneuvering of human activities. The ideas and thoughts are evolving in different time interval in the quest of better life. However, dissatisfactions are emerging and education, as initiator and being the instrument of change, has not been able to control over these dissatisfactions. There are much evidences of antagonistic events. conflicts are emerging in diverse forms and shapes in different parts of the world. Current social practices have created power centers in every societies. The foremost trend appearing right now is the race for controlling the resources and creation of wealth. This kind of trend prevailing in the society is detrimental in attaining satisfaction and happiness. Apart from this, rapid advancement of technology has caused dynamic changes in the culture and social behaviors. The cultural dimensions are taking new shapes owing to technology. In this adverse condition, education is under tremendous criticism. This is true that education creates knowledge & skill to the individuals, but it also sensitizes the societal issues. In this context, education is at the center of politics and many scholars consider education and politics complementary to each other. This signifies that education is an integral part of society and it has connection with the government or public affairs of a country. Visualizing the global and local conflicts, present system of education has not proved capable in generating type of knowledge that is relevant to today’s changing society. The direction of education is especially important to establish peace and harmony in the society. Therefore, there is a need of rethinking rational model of education. The methodology adopted in the paper is the extensive review of the literature and The comprehensive study of societal issues appearing in the society. Besides, the experience of the author in the academia is also contributing to the preparation of the paper.